Frequency of red blood cell alloimmunization in sickle cell patients and healthy donors: the influence of racial and antigenic pattern differences - Vafaei, Majid; Keikhaei-dehdazi, Bijan (International Journal Of Community Medicine And Public Health, 2017)
Background: Red blood cell (RBC) transfusions are frequently used in patients with sickle cell disease (SCD) to treat and prevent of their disease complications. However repeated blood transfusions are often complicated by RBC alloimmunization. Race and antigenic pattern differences are the common risk factor to develop alloimmunization. This study was performed to determine the frequency of RBC alloimmunzation in sickle cell patients and healthy blood donors. Methods: This is a cross sectional study that has been done on 140 patients with SCD and 140 healthy blood donors from April 2015 to April 2016. The RBC phenotype of all patients and donors investigated by Tub method and all panel test phases were done at immunohematology laboratory of Iranian Blood Transfusion Organization of Ahwaz. Results: Of all SCD patients 61 (43.6%) were male and 79 (56.4%) were female. 68 (48.5%) were HbSS and 72 (51.4%) were S/B thalassemia. The mean age of patients was 19.69 (range: 2-60) years. Of all patients, 114 (81.25%) had received transfusion. The RBC alloimmunization rate among SCD patients was 7.1% and 50% of the RBC alloimmunization had anti-Kell and 30% had anti-Rh. The comparison of the RBC phenotypes between the group of patients with SCD and the group of blood donors (non-Arab) revealed a statistically significant difference in the frequency of S (54% vs. 67%, p=0.024), M (82.7% vs. 90.7%, p=0.049), and FYb (73.4% vs. 55.7%, p=0.002). Conclusions: Althoguh alloimmunization rate in SCD patients in this study was lower than reported by other studies but cross matchining at least for the Rh and Kell systems from the time of initial transfusion may decrease the incidence of alloimmunization.